C⁎-Algebra-Valued G-Metric Spaces and Related Fixed-Point Theorems. (12th July 2018) - Shen, Congcong; Jiang, Lining; Ma, Zhenhua
Abstract : We introduce the notion of theC ⁎ -algebra-valuedG -metric space. The existence and uniqueness of some fixed-point theorems for self-mappings with contractive or expansive conditions on completeC ⁎ -algebra-valuedG -metric spaces are proved. As an application, we prove the existence and uniqueness of the solution of a type of differential equations.